2014
DOI: 10.1001/jamaophthalmol.2014.2333
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events and Bleeding Risk Associated With Intravitreal Antivascular Endothelial Growth Factor Monoclonal Antibodies

Abstract: IMPORTANCE Few data exist regarding the systemic safety of intravitreal antivascular endothelial growth factor (anti-VEGF) monoclonal antibody (mAb).OBJECTIVE To conduct a systematic review and meta-analysis to evaluate the risk of major cardiovascular and nonocular hemorrhagic events in patients with neovascular age-related macular degeneration (AMD), diabetes mellitus-associated macular edema (DME), or retinal vein occlusions (RVOs) who receive intravitreal anti-VEGF mAbs.DATA SOURCES The MEDLINE and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 57 publications
1
80
2
1
Order By: Relevance
“…11,13 Thulliez et al concluded that intravitreal anti-VEGF antibodies did not result in statistically significant increases in major cardiovascular or systemic hemorrhages, but agreed that ''studies and meta-analyses were not powered enough to correctly assess these risks''. 45 Thus, caution is still urged for patients receiving intravitreal injections of anti-VEGF antibodies who are especially at risk for systemic adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Thulliez et al concluded that intravitreal anti-VEGF antibodies did not result in statistically significant increases in major cardiovascular or systemic hemorrhages, but agreed that ''studies and meta-analyses were not powered enough to correctly assess these risks''. 45 Thus, caution is still urged for patients receiving intravitreal injections of anti-VEGF antibodies who are especially at risk for systemic adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Its use is now extremely limited. 51 Although anti-VEGF treatments have been suspected to increase the risk of systemic arterial thromboembolic events [52][53][54][55] and intraocular pressure, 56-59 the results of clinical trials are still inconclusive. The risks of intravitreal anti-VEGF drugs in pregnant or lactating women have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Despite ample research and large meta-analyses demonstrating little systemic risk with anti-VEGF treatments in most patients, [23][24][25][26][27] clinicians should be mindful of these agents in this higher-risk population. A recent meta-analysis looking specifically at diabetic patients with intensive (monthly for 2 years) intravitreal anti-VEGF injections found an increased risk of death and potentially cerebrovascular accidents, although not myocardial infarction or arteriothrombotic events, in this high-risk group.…”
Section: Safetymentioning
confidence: 99%